How do you solve #3x - 2y = 0# and #x = 11 - 3y# using substitution?

1 Answer
Mar 7, 2018

Answer:

#(2,3)#

Explanation:

Substitution is the process of solving a system of equations, using one equation with a solved variable in place of that variable in the second equation.

Here are the equations we are given:

#3x-2y=0#
#x=11-3y#

Luckily, we already have one variable solved for. All we have to do is replace the #x# in the first equation with its corresponding value.

We should now have this:

#3(11-3y)-2y=0#

From here, we simply solve for #y#:

#3(11-3y)-2y=0#

#33-9y-2y=0#

#33-11y=0#

#-11y=-33#

#y=(-33)/-11#

#y=3#

Now that we know our #y# value, we can plug it back into the "#x#" equation.

#x=11-3(3)#

#x=11-9#

#x=2#